The effects of physical activity on glutamate neurotransmission in neuropsychiatric disorders - Baskerville, Richard; McGrath, Thomas; Castell, Lindy (Frontiers in Sports and Active Living, 2023)
Physical activity (PA) is an effective way of increasing cognitive and emotional health and counteracting many psychiatric conditions. Numerous neurobiological models for depression have emerged in the past 30 years but many struggle to incorporate the effects of exercise. The hippocampus and pre-frontal cortex (PFC) containing predominantly glutamate neurotransmission, are the centres of changes seen in depression. There is therefore increasing interest in glutamatergic systems which offers new paradigms of understanding mechanisms connecting physical activity, stress, inflammation and depression, not explained by the serotonin theories of depression. Similar hippocampal glutamate dysfunction is observed in many other neuropsychiatric conditions. Excitatory glutamate neurones have high functionality, but also high ATP requirements and are therefore vulnerable to glucocorticoid or pro-inflammatory stress that causes mitochondrial dysfunction, with synaptic loss, culminating in depressed mood and cognition. Exercise improves mitochondrial function, angiogenesis and synaptogenesis. Within the glutamate hypothesis of depression, the mechanisms of stress and inflammation have been extensively researched, but PA as a mitigator is less understood. This review examines the glutamatergic mechanisms underlying depression and the evidence of physical activity interventions within this framework. A dynamic glutamate-based homeostatic model is suggested whereby stress, neuroinflammation and PA form counterbalancing influences on hippocampal cell functionality, which manifests as depression and other neuropsychiatric conditions when homeostasis is disrupted.